Discourses on social software - Eijck, J. van (Jan); Verbrugge, Rineke (Texts in logic and games ;, 2009)
This book offers the reader an ideal introduction to the exciting new field of social software. It shows in detail the many ways in which the seemingly abstract sciences of logic and computer science can be put to use to analyse and solve contemporary social problems.